Mobile-based collaborative interventions between target participants and circle participants - Silva, Joab Cavalcante da; Dantas, Laurentino Augusto; Di Marzo, Marina Ariane D.; Rodrigues, Kamila Rios; Pimentel, Maria da Graça C. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.243939, 2024)
The literature registers the use of mobile devices in interventions that gather information from individual participants within their natural environments. Researchers have identified a need for supporting interventions that involve both participants and individuals within their social circles. To address this need, we conducted a Rapid Systematic Review focused on the following questions: Which papers describe models that enable experts to foster collaboration among group members in interventions mediated by mobile devices or IoT? Which studies present operations related to communication, cooperation, or coordination? How were these solutions developed and evaluated? What roles do participants assume within the interventions? In which domains were these evaluations conducted? The review selected 26 works, most within the domains of Education, Health, or both (84%). The analysis revealed significant gaps in the literature regarding systems and models that facilitate communication, cooperation, or coordination among intervention participants and their social circles. This analysis indicated the need for a set of functional and non-functional requirements to guide the design and evaluation of future solutions. We contribute by proposing these requirements to address the identified gaps and enhance the development of effective intervention systems.